Water column raw data (Kongsberg EM 122 entire dataset) of RV SONNE during cruise SO310 - Sebastian Krastel; Rachel Barrett; Jörg Bialas; Mia Schumacher (PANGAEA, 2025)
Raw water column data were collected aboard RV SONNE during cruise SO310 using a Kongsberg EM 122 multibeam echosounder. The expedition took place during 20.02.2025 - 22.03.2025 from Wellington (New Zealand) – Wellington (New Zealand) in the South Pacific Ocean. The main scientific aim of SO310 was to compare canyon systems from a passive and an active margin off New Zealand (Palliser and Pegasus Canyon) and to develop frequency-volume relationships of landslides in canyons with special focus on systematic differences between active and passive margin settings. In addition, factors controlling the size and location of failures including topographic amplification effects of canyons for earthquake waves will be investigated. The integrated analysis of the data shall lead to an improved assessment of hazards and risks related to sediment failures in canyons at active and passive margins. Data were recorded within the EEZ of New Zealand. Sound velocity profiles (SVP) were applied on the data for calibration. Please see environmental data and the cruise report for details. The data are unprocessed and can therefore contain incorrect depth measurements (artifacts) if not further processed. Note that refraction errors may occur when no proper SVP is applied. Acquisition and provision of the data are part of the DAM Underway Project and published according to the FAIR principles.